1997
DOI: 10.1111/1467-9450.00018
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological course after surgery for intracranial aneurysms. A prospective study and a critical review

Abstract: Previously, only three studies with representative samples of patients with ruptured intracranial aneurysms have provided detailed results of prospective, repeated, neuropsychological assessments after surgery. These studies apparently disagree with regard to occurrence of cognitive deficits and to degree of improvement between early and delayed follow-ups. The present paper attempts to analyze the conditions underlying these differences in results. As a first step in this analysis we present a comprehensive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(64 reference statements)
0
12
0
1
Order By: Relevance
“…Perhaps the most important is that our follow-up period was only 3 months, and many participants were probably still in the active phase of recovery. 5,9 Analysis after a longer period of follow-up is needed to determine whether the cognitive deficits we identified persisted in the long term; this will be the subject of a future report. Second, although one study found that a large proportion of SAH patients suffer from role limitations related to physical problems, 37 it is unclear to what extent cognitive dysfunction after SAH affects health-related quality of life.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Perhaps the most important is that our follow-up period was only 3 months, and many participants were probably still in the active phase of recovery. 5,9 Analysis after a longer period of follow-up is needed to determine whether the cognitive deficits we identified persisted in the long term; this will be the subject of a future report. Second, although one study found that a large proportion of SAH patients suffer from role limitations related to physical problems, 37 it is unclear to what extent cognitive dysfunction after SAH affects health-related quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…Many investigators have evaluated the effect of aneurysm location on cognitive function after SAH, 5,7-9,23,24,26,28,32,34 -36 but few have reported significant associations; aneurysms of the anterior communicating artery, 34 vertebrobasilar system, 8 and left anterior circulation 9 have previously been associated with poor cognitive outcome. In our study, posterior circulation aneurysms were associated with better performance in 7 of 8 domains in the univariate analyses and in both memory domains in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,26 The influence of other factors such as hydrocephalus, aneurysm location, treatment method, vasospasm, and ischemic complications on neurocognitive sequelae are less clear. 10,12,16,28 These pathological processes are acute or subacute issues and would not be expected to lead to permanent deficits in the absence of ischemic damage to the neural tissue. However, evidence that physiopathological changes in the acute phase of aSAH do not lead to permanent functional neuronal change is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Ана-лиз ближайших функциональных исходов свиде-тельствует о наличии когнитивных расстройств разной степени выраженности у 59% больных на момент выписки из стационара [4]. 60-70% больных, состояние которых до операции было 1-3 балла по шкале Hunt-Hess, в послеопераци-онном периоде не имеют тяжелых когнитивных расстройств, нарушавших психосоциальную адаптацию [5]. В восстановительном периоде заболевания когнитивные расстройства име-ют 65% пациентов [6].…”
Section: âведениеunclassified